Biblical Foundations of Synodity in the Church - Rivas, Luis Heriberto (Teología, 2019)
In March 2018, the International Theological Commission offers a Document called "The Synod of Life and Mission of the Church". With it, he wants to accompany the pope’s initiative to make our community a Synodal Church, a Church in the process of leaving, where everything is impregnated by the call to evangelize. This text is not a comment to said document but it is located in that search. This collaboration of Father Luis Heriberto Rivas proposes the biblical keys to understand synodality as a key to the identity of the Church